The impact of level of education on vascular events and mortality in patients with type 2 Diabetes mellitus: results from the ADVANCE study - Blomster, J; Zoungas, S; Woodward, M; Neal, B; Harrap, S; Poulter, N; Marre, M; Williams, B; Chalmers, J; Hillis, G (Elsevier, 2017)
Aims The relationship between educational level and the risk of all-cause mortality is well established, whereas the association with vascular events in individuals with type 2 diabetes is not well described. Any association may reflect a link with common cardiovascular or lifestyle-based risk factors. Methods The relationships between the highest level of educational attainment and major cardiovascular events, microvascular complications and all-cause mortality were explored in a cohort of 11,140 individuals with type 2 diabetes. Completion of formal education before the age of 16 was categorized as a low level of education. Regional differences between Asia, East Europe and Established Market Economies were also assessed. Results During a median of 5 years of follow up, 1,031 (9%) patients died, 1,147 (10%) experienced a major cardiovascular event and 1,136 (10%) a microvascular event. After adjustment for baseline characteristics and risk factors, individuals with lower education had an increased risk of cardiovascular events (hazard ratio (HR) 1.31, 95% CI 0.1.16–1.48, p<0.0001), microvascular events (HR 1.23, 95% CI 1.09–1.39, p=0.0013) and all-cause mortality (HR 1.34, 95% CI 1.18–1.51, p<0.0001). In regional analyses the increased risk of studied outcomes associated with lower education was weakest in Established Market Economies and strongest in East Europe. Conclusions A low level of education is associated with an increased risk of vascular events and death in patients with type 2 diabetes, independently of common lifestyle associated cardiovascular risk factors. The effect size varies between geographical regions.